Intra- and inter-specific effects in prey size capture by wolf spiders (Araneae: Lycosidae) against the fall armyworm Spodoptera frugiperda under laboratory conditions - García, Luis Fernando; Velasco, Andrés; Colmenárez, Yelitza C. [UNESP]; Pétillon, Julien; Cantor, Fernando (Taylor & Francis, 2022)
The fall armyworm, Spodoptera frugiperda, (hereafter FAW) is a major pest in South American crops; however, knowledge about its potential native natural predators is limited. Size is a factor that constrains predators against prey, such as larvae of varying sizes. The predation capability of males and females of the native wolf spiders Lycosa thorelli and Pavocosa sp. were evaluated against different-sized FAW larvae. Contrary to expected results, both sexes consumed FAW larvae of similar size ranges. L. thorelli captured larger FAW larvae, suggesting this species might prey on a wider range of FAW instars indicating its potential role as a FAW biological control agent.
Keywords: generalist predator; native; natural enemies; pest; Relative size